Entrance of the Bijolia temple complex - Temples of India Project Team (Jio Institute, 2024)
From the entrance of the Bijolia temple complex, both the Mahakal Temple and the Hazareshwar Temple are visible. The Hazareshwar Temple, facing east, reveals its rear facade, while the Mahakal Temple, oriented westward, presents its entrance to those arriving in the complex.